Rockburst Inducement Mechanism and Its Prediction Based on Microseismic Monitoring - Yongsong Li; Chao Zhou (Geofluids)
The rockburst disaster in the hard rock caused by excavation and unloading of deep underground caverns threatens the safety of engineering construction. In recent years, the microseismic monitoring technology, which can dynamically monitor the whole process of progressive failure of rock mass in real time, has been widely used in rockburst monitoring and early warning of underground engineering. In view of the slight rockburst in local surrounding rock during the excavation of underground powerhouse of Huanggou Pumped Storage Power Station, a rockburst microseismic monitoring system is constructed. And through the analysis of the temporal and spatial activity of microseisms during the monitoring period, the potential risk areas of rockbursts are identified and delineated. The monitoring results show that the microseismic system can effectively capture the blasting and microseismic signals during construction. The microseismic activity is closely related to the intensity of field blasting disturbance. The potential risk areas of rockburst are the upstream side arch shoulder and the intersection between lower drainage corridor and workshop installation room. The research results can provide technical support for later excavation and support of underground powerhouse caverns of Huanggou Hydropower Station.